IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER ISLAMI DALAM MEWUJUDKAN AKHLAK PESERTA DIDIK DI SDIT TAHFIZH QUR'AN AL-JABAR TELUKJAMBE BARAT KARAWANG - Lala Nurlatifah; Astuti Darmiyanti; Dewi Siti Aisyah (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
A bad moral that continues and seems increasingly out of control and undirected. Impairment of personal qualities that are not good by the successor of this nation occurs in all aspects, ranging from speaking, how to dress and also behavior. For that character education is very important to be instilled especially in schools by using the management of character education itself well.           This study aims to determine the implementation of character education management in SDIT Tahfizh Qur'an Al-Jabar Telukjambe Barat Karawang in an effort to realize the morals of students. use the description method with a qualitative approach. Data collection is done by documentation, observation, interviews related to the object being examined. Then analyzed using qualitative descriptive analysis.           The results of this study are that (1) Planning for character education at SDIT Tahfizh Qur'an is carried out through a meeting at the beginning of the year by involving many parties both teachers, staff, other employees and parents (2) implementing character education at SDIT Tahfizh Qur'an Al-Jabar through integration of character values into subject matter, teacher training by inviting experts, curriculum additions or improvements, teacher habituation and exemplary (3) evaluation (assessment) of character education management in SDIT Tahfizh Qur'an Al-Jabar ie the principal evaluates one week two times to each class and students are given an evaluation book when doing activities at home.